2018
DOI: 10.1159/000486429
|View full text |Cite
|
Sign up to set email alerts
|

The International Caries Detection and Assessment System – ICDAS: A Systematic Review

Abstract: The aims of this study were: (1) to evaluate the overall reproducibility and accuracy of the International Caries Detection and Assessment System (ICDAS) for assessing coronal caries lesions, and (2) to investigate the use of systems associated with the ICDAS for activity assessment of coronal caries lesions. Specific search strategies were adopted to identify studies published up to 2016. For the first objective, we selected studies that assessed primary coronal caries lesions using the ICDAS as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
90
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(106 citation statements)
references
References 65 publications
3
90
0
4
Order By: Relevance
“…Our results that, compared with OW, NW children have higher prevalence of dental caries at both ICDAS thresholds (“EC/DC” and “DC”) reject the null hypothesis of this investigation. A recent systematic review revealed considerable performance of the ICDAS visual criteria for evaluating carious lesions and encouraged its use in clinical practice . It should be pointed out that the use of different ICDAS thresholds may influence diagnostic accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…Our results that, compared with OW, NW children have higher prevalence of dental caries at both ICDAS thresholds (“EC/DC” and “DC”) reject the null hypothesis of this investigation. A recent systematic review revealed considerable performance of the ICDAS visual criteria for evaluating carious lesions and encouraged its use in clinical practice . It should be pointed out that the use of different ICDAS thresholds may influence diagnostic accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…In daily clinical practice, this evaluation is mainly performed by visual examination because this method has good overall performance . Systems for caries activity status assessment have shown moderate values concerning reproducibility and overall performance . Nevertheless, many aspects could have influence on the performance of visual examination, as examiners’ training .…”
Section: Discussionmentioning
confidence: 99%
“…10 Systems for caries activity status assessment have shown moderate values concerning reproducibility and overall performance. 28 Nevertheless, many aspects could have influence on the performance of visual examination, as examiners' training. 10 This could be crucial mainly because undergraduate students have not developed their diagnostic skills yet.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review reported visual inspection to have good accuracy for visual inspection, which was further improved when used in conjunction with a detailed and validated index . Meticulous caries diagnostic methods, such as the International Caries Detection and Assessment System (ICDAS), meet this requirement, having been demonstrated to have high validity and reproducibility …”
Section: Introductionmentioning
confidence: 99%
“…8 Meticulous caries diagnostic methods, such as the International Caries Detection and Assessment System (ICDAS), meet this requirement, having been demonstrated to have high validity and reproducibility. 6,[9][10][11] Bitewing radiographs provide an additional diagnostic yield, especially for proximal caries, where direct visual examination is not possible. 12 Bitewing radiographs, however, show where the lesion is anatomically, in enamel or dentine, but do not confirm the presence of cavitation which is the threshold between operative and nonoperative intervention.…”
Section: Introductionmentioning
confidence: 99%